KONTEKSTUALISASI HUKUM ZAKAT DI INDONESIA (STUDI TENTANG LEGISLASI DAN KONSTITUSIONALITAS UU PENGELOLAAN ZAKAT DALAM PERSPEKTIF SIYÂSAH SYAR’IYYAH) - A, Asmawi; Faizin, Afwan (Universitas Islam Negeri Mataram, 2017)
This article aims to discuss the enactment of Zakat ManagementLaw 23/2011. Based on the critical textual study, this study proposes an analysisshowing that the legislation of this law come out of centestation by variousinterest from different groups. Substantially, this law does not contravenethe Constitution of 1945 so that is has a very strong constitutional ground.Siyasashar’iyya is here relevant to the legislation of Islamic law, including theLaw of Zakat Management 23/2011. Therefore, this law is a real example ofthe product of the politics of Islamic law in the context of Indonesia. Artikel ini akan menjelaskan bahwa legislasi UU 23/2011 (UUPZ)merupakan suatu proses politik yang menghadirkan kontestasi kepentingan/aspirasi berbagai pihak. UU 23/2011 (UUPZ) secara umum tidak bertentangandengan UUD 1945 sehingga memiliki daya konstitusionlitas yang relatif kokoh.Teori siyâsah syar’iyyah memiliki relevansi yang kuat dengan isu legislasi dankonstitusionalitas UU 23/2011 (UUPZ). UU 23/2011 (UUPZ) merupakanproduk dari siyâsah syar’iyyah dalam konteks keindonesiaan.